STRESS AND STRAIN STATE OF THE KAZAKH SHIELD FROM THE EARTHQUAKE FOCAL MECHANISMS DATA - A. N. Uzbekov; N. N. Poleshko (Геодинамика и тектонофизика)
The paper presents the results obtained during the study of seismicity of the Kazakh shield based on the data from seismic stations of the Institute of Geophysical Researches of Kazakhstan which are a part of the international monitoring systems. Emphasis has been placed on seismic activation in 2016–2018 in the middle part of the Central Kazakhstan arch, previously considered aseismic. The earthquake focal mechanisms determined for 40 seismic events recorded in the investigated area are based on the displacement directions of the first arriving P waves.On the basis of the analysis of the earthquake focal mechanism data set, an assessment has been made of the present-day stress-strain state of the Earth’s crust of the low-seismicity Kazakh shield. It is shown that a system of stresses in the investigated area is characterized by conditions for near-horizontal compression whose direction is consistent with the direction of movement of the Alpine geomorphostructures. It has been found that the earthquake sources in the investigated area are dominated by reverse faults and reverse-slip faults which correspond structurally to the northeast-striking and submeridional tectonic faults, thus testifying to present-day seismic activation of the northeastern thrusts.This study allowed for concluding that the seismic events considered are human-induced, i.e. technogenic-tectonic, earthquakes. A long-term technogenic impact reducing the strength of rocks in fault zones can be a cause of critical stress drop in earthquake sources located in the Kazakh shield. The data on the character of motions and stresses in the earthquake sources influencing on shaking intensity will be used in combination with other methods for the assessment of natural and technogenic hazards related to geodynamic processes.